11. For arbitrary constants c1,c2, And c3 show that an=c12n+c25n+c3n5n satisfies the recurrence relations an-12an-1+45an-2-50an-3=0
To prove "a_n=c_12^n+c_25^n+c_3n5^n" Â satisfies the recurrence relation "a_n-12a_{n-1}+45a_{n-2}-50a_{n-3}=0", it is enough to show that the solution of the recurrence relation is "a_n=c_12^n+c_25^n+c_3n5^n".
The auxiliary equation of the recurrence relation is, "r^3-12r^2+45r - 50 =0."
Using synthetic division,
"\\begin{array}{l|lll}\n2&1&-12&~~~45&-50\\\\\n& 0 & ~~~~~2 & -20 & ~~~50\\\\\n\\hline\n& 1 & -10 & ~~~25 & \\mid 0\\\\\n\\hline\n\\end{array}"
We get 2 is a root of the equation. Hence,
"\\begin{aligned}\n0 = r^3-12r^2+45r - 50 &= (r-2)(r^2-10r+25)\\\\\n&=(r-2)(r-5)^2\n\\end{aligned}"
Thus the roots of the auxiliary equation are, "r=2,5,5".
The solution of the recurrence relation is
"a_{n} = c_12^n + (c_2 + c_3n)5^{n} = c_12^n + c_25^{n} + c_3n5^{n}". Hence "a_{n}" satisfies the given recurrence relation.
Comments
Leave a comment